Perumusan Strategi Guna Peningkatan Daya Saing Sekolah Menengah Kejuruan Ma’arif NU 02 Bumiayu - Sumi Nurmayatin; Sutarmin Sutarmin (Universitas Peradaban, 2016)
The aims of this research are to: 1) identify the internal factor that can increase the competitiveness of SMK Ma’arif NU 02 Bumiayu, 2) analyze the internal factor that can increase the competitiveness of SMK Ma’arif NU 02 Bumiayu, 3) identify the external factor that can increase the competitiveness of SMK Ma’arif NU 02 Bumiayu, 4) analyze the external factor that can increase the competitiveness of SMK Ma’arif NU 02 Bumiayu, 5)formulate the alternative strategy to increase competitiveness Position of SMK Ma’arif NU 02 Bumiayu. The technique of data analysis uses SWOT (Strength, Weakness, Opportunities, Threats), and continued by using Quantitative Strategic Planning Matrix (QPSM) as a instrumen to determine the most apropiate strategy to increase competitiveness Position of SMK Ma’arif NU 02 Bumiayu. This research is a qualitative research by doing deeply interview to the vice principal of curriculum, teacher, and staff of SMK Ma’arif NU 02 Bumiayu. Furthermore, the data collection also taken by observation, focus group discusion, documentation and literature review. The result of the research showed that based on cartesius diagram the result of internal and external obtained main strategy in the form of growth strategy, Furthermore, based on QSPM could be concluded some best strategies of the other alternative strategies, : 1) intensify promotion, 2) increasing the quality of human resource, 3)funds allocation based on priority scale, 4) utilitize the facilities and infrastructures well.